Conceptual Change Textbook Based on Local Wisdom of Palembang on Heat and Temperature - Saparini Saparini; Syuhendri Syuhendri; Murniati Murniati (Universitas Lambung Mangkurat, 2021)
The misconception is one of the learning difficulties that occur in students when learning physics, especially the concepts of heat and temperature. One solution to overcome this is by using a textbook based on conceptual change. The purpose of the research is to develop a valid and practical conceptual change textbook based on the local wisdom of Palembang. This study uses the Rowntree research method and is combined with Tessmer's evaluation at the evaluation stage. Data was collected through a walkthrough and questionnaire. The data were analyzed by looking for the mean score obtained and then converted according to the category of expert validation results and the product practicality level. The results showed that the product developed was categorized as very valid in every aspect of content, language, and design. Meanwhile, the results of the one-to-one and small group evaluation stages each showed that it is practical. This shows that the product developed is suitable to be used and by applying appropriate learning methods expected to reduce students' misconceptions of temperature and heat.